Bilateral tonic pupils: Holmes–Adie syndrome or generalised neuropathy? - Bremner, F D (BMJ Group, 2007)
AIM: To compare the pupil signs in patients with bilateral pupillotonia caused by Holmes–Adie syndrome or generalised peripheral neuropathy. METHODS: Infrared video pupillographic techniques were used to measure a number of pupil variables in patients with Holmes–Adie syndrome, generalised neuropathy (various aetiologies) and healthy age‐matched control subjects. RESULTS: Regardless of aetiology, the patients generally had pupil signs typical of pupillotonia (small dark diameters, large light diameters, tonic near responses, attenuated light responses with light‐near dissociation, and sector palsy). However, significant differences were found in the prevalence and magnitude of several pupil variables in the two patient groups. In particular, sector palsy and anisocoria exceeding 1 mm (in the light) were seen much more commonly in Holmes–Adie patients than patients with generalised neuropathy. The presence of both these pupil signs can be used to distinguish between these diagnoses with a sensitivity of 58% and a specificity of 90%. CONCLUSIONS: The tonic pupils of patients with Holmes–Adie syndrome are significantly different to those found in patients with generalised neuropathy; recognition of these differences may allow distinction between these diagnoses.